Association Between Hematological Parameters and Iron Metabolism Response After Marathon Race and ACTN3 Genotype - Sierra, Ana Paula Renno; Oliveira, Rodrigo Assunção; Silva, Elton Dias; Lima, Giscard Humberto Oliveira; Benetti, Marino Pereira; Kiss, Maria Augusta Pedanti; Sierra, Carlos Anibal; Ghorayeb, Nabil; Seto, Jane T.; Pesquero, João Bosco; Cury-Boaventura, Maria Fernanda (Frontiers in Physiology, 2019)
α -Actinin-3 (ACTN3 R577X, rs.1815739) polymorphism is a genetic variation that shows the most consistent influence in metabolic pathway and muscle phenotype. XX genotype is associated with higher metabolic efficiency of skeletal muscle, however the role of ACTN3 polymorphism in oxygen transport and utilization system has not yet been investigated. Therefore, the aim of this study was to determine the influence of ACTN3 polymorphisms on hematological and iron metabolism response induced by marathon race. Eighty-one Brazilian amateurs male endurance runners participated in the study. Blood samples and urine were collected before, immediately after, one, three and fifteen days after the marathon race. Urine, hematological parameters, iron metabolism and ACTN3 genotyping analyses were performed. The marathon race induced a decrease on erythrocytes, Hb and Ht, an increase on hematuria, creatinine, myoglobin, red cell distribution width, mean corpuscular hemoglobin concentration, mean corpuscular hemoglobin, direct and indirect bilirubin and erythropoietin. Moreover, an elevation immediately or one day after the marathon race follows a reduction three or fifteen days after the marathon race were observed on transferrin saturation and iron and transferrin levels. Hematological parameters and iron metabolism changes-induced by marathon race were not observed in XX genotypes. Hematuria and decreased erythrocytes, Hb, Ht and iron and transferrin levels were observed only in RR and/or RX genotypes but not in XX genotypes. The percentage of runners with hematuria, leukocyturia, iron deficiency, creatinine, myoglobin and bilirubin unbalance was higher in RR compared to XX genotypes. ACTN3 polymorphism is associated with iron metabolism and hematological responses after endurance exercise. Despite these results are based on a small sample they highlight a protective role of the XX genotype on hematological and renal changes induced by long-distance exercise. Therefore these findings should be further replicated.